Effects of coronavirus disease 2019 (COVID-19) pandemic on antimicrobial prevalence and prescribing in a tertiary hospital in Singapore - Ng, Tat Ming (2021)
Background: The deployment of antimicrobial stewardship (AMS) teams to deal with the COVID-19 pandemic can lead to a loss of developed frameworks, best practices and leadership resulting in adverse impact on antimicrobial prescribing and resistance. We aim to investigate effects of reduction in AMS resources during the COVID-19 pan-demic on antimicrobial prescribing. Methods: One of 5 full-time equivalent AMS pharmacists was deployed to support pandemic work and AMS rounds with infectious disease physicians were reduced from 5 to 2 times a week. A survey in acute inpatients was con-ducted using the Global Point Prevalence Survey methodology in July 2020 and compared with those in 2015 and 2017–2019. Results: The prevalence of antimicrobial prescribing (55% in 2015 to 49% in 2019 and 47% in 2020, p = 0.02) and antibacterials (54% in 2015 to 45% in 2019 and 42% in 2020, p < 0.01) have been reducing despite the pandemic. Antimicrobial prescribing in infectious disease wards with suspected or confirmed COVID-19 cases was 29% in 2020. Overall, antimicrobial prescribing quality indicators continued to improve (e.g. reasons in notes, 91% in 2015 to 94% in 2019 and 97% in 2020, p < 0.01) or remained stable (compliance to guideline, 71% in 2015 to 62% in 2019 and 73% in 2020, p = 0.08). Conclusion: During the COVID-19 pandemic, there was no increase in antimicrobial prescribing and no significant differences in antimicrobial prescribing quality indicators.